Optimized Nitrogen Foam Flooding System for Enhanced Oil Recovery: Development and Field Test in Mu146 Block Medium-High Permeability Reservoir, China - Jia-Yang Luo; Zhen-Jun Wang; Xin-Yuan Zou; Quan Xu; Bo Dong; Song-Kai Li; Zhu-Feng Wang; Jie-Rui Liu; Xian-Feng Wang; Xiao-Hu Xue (Energies)
This study presents a tailored nitrogen foam flooding system developed for the Mu146 block’s medium-high permeability reservoir conditions. Through systematic optimization, we establish an optimal formulation comprising 0.40% FP2398 foaming agent and 0.13% WP2366 stabilizer. The formulated foam demonstrates superior performance characteristics with a generated volume of 850 mL and extended stability duration of 1390 s, exhibiting exceptional structural integrity under oil-bearing conditions. Core flooding experiments conducted on berea cores reveal a 33.20% incremental oil recovery factor following waterflooding that achieves 53.60% primary recovery. The non-steady-state nitrogen foam huff-and-puff (NSSNFHF) field test at Well Mu146-61 shows significant reservoir response, with post-treatment analyses indicating an average chloride ion concentration increase of 540.20 mg/L and total salinity elevation of 1194.20 mg/L across five monitoring wells. These chemical signatures confirm effective volumetric sweep enhancement through the NSSNFHF field test, demonstrating a flooding-like mechanism that mobilizes bypassed oil in previously unswept zones. The field test encompassing Well Mu146-61 and four offset producers yield substantial production improvements, including a 74.55% increase in fluid production rates and a sustained oil yield of 1.80 tons per day. The validity period of the NSSNFHF field test is more than 12 months. The technology demonstrates dual functionality in conformance control and enhanced recovery, effectively improving both oil productivity and ultimate recovery factors.